Aplikasi Pemesanan Tempat Restoran Kota Palembang - Irma Salamah; Nasron Nasron; Nurul Hidayah Shafariah (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Palembang is the capital of the province of South Sumatra that has a diverse culture, beautiful tourist attractions and has a distinctive culinary flavor. Usually, culinary tourism becomes the main attraction for tourists when visiting an area. Culinary attractions that are often visited by tourists such as restaurants, restaurants, cafes, etc. This application aims to help staff handle orders from the surge of tourists who arrive, as well as help and make it easier for tourists to find restaurant information, restaurant places, place bookings, and choose the desired menu. This application is an ordering application for a restaurant in the city of Palembang that uses Android as a data communication process and uses notifications as its statement. This application was built using the waterfall method as an application development method so that it can facilitate the design process. This application is expected to facilitate tourists and employees in the process of booking a place in the city of Palembang.